2015
DOI: 10.1038/srep18117
|View full text |Cite
|
Sign up to set email alerts
|

Stanniocalcin-1 inhibits thrombin-induced signaling and protects from bleomycin-induced lung injury

Abstract: Thrombin-induced and proteinase-activated receptor 1 (PAR1)-mediated signaling increases ROS production, activates ERK, and promotes inflammation and fibroblast proliferation in bleomycin-induced lung injury. Stanniocalcin-1 (STC1) activates anti-oxidant pathways, inhibits inflammation and provides cytoprotection; hence, we hypothesized that STC1 will inhibit thrombin/PAR1 signaling and protect from bleomycin-induced pneumonitis. We determined thrombin level and activity, thrombin-induced PAR-1-mediated signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Among chemokines, CXCL16, CCL21 and CXCL14 were present in high concentrations in Exosomes d-MAPPS sample (Figure 2A). Each of these molecules is crucially involved in the pathogenesis of lung, synovial, and eye inflammation (51)(52)(53)(54)(55)(56)(57). Bronchial epithelium is an important source of CXCL16 (51) while its receptor CXCR6 is highly expressed on lung-infiltrated T cells (51).…”
Section: Discussionmentioning
confidence: 99%
“…Among chemokines, CXCL16, CCL21 and CXCL14 were present in high concentrations in Exosomes d-MAPPS sample (Figure 2A). Each of these molecules is crucially involved in the pathogenesis of lung, synovial, and eye inflammation (51)(52)(53)(54)(55)(56)(57). Bronchial epithelium is an important source of CXCL16 (51) while its receptor CXCR6 is highly expressed on lung-infiltrated T cells (51).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we employed a superoxide generator (paraquat) and a cell-permeable superoxide dismutase mimetic (MnTBAP) in our assays (20). As shown, treatment with MnTBAP and paraquat did not appear to prominently alter the effects of PMA on U937 cell aggregation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Exactly how STC-1 differentially regulates CD14 and various TLRs is still not entirely clear but could be accredited to its ability to shift the balance of competing mitogen-activated protein kinase (MAPK) pathways such as ERK1/2 and p38. For instance, STC-1 can suppress ERK1/2 signaling (20, 48) and, therefore, decrease PMA-induced TLR4/CD14 expression which is dependent on ERK1/2 (49), while perhaps enhancing p38 activity which is important for TLR2 expression under some circumstances (50). Alternatively, the conserved calcium-regulatory properties of STC-1 might be implicated as CD14 expression is sensitive to calcium chelation and calcium channel antagonists (51).…”
Section: Discussionmentioning
confidence: 99%
“…Stanniocalcin-1 (STC-1) is a unique multifunctional protein that is cellular protective in a variety of tissues including intestine (Wu et al, 2014), heart (Mohammadipoor et al, 2016; Shi et al, 2014; Westberg et al, 2007a), lung (Huang et al, 2015b; Tang et al, 2014), kidney (Huang et al, 2012; Huang et al, 2014; Huang et al, 2015a; Liu et al, 2016; Pan et al, 2015), cerebral neurons (Durukan Tolvanen et al, 2013; Westberg et al, 2007b; Zhang et al, 2000), retinal photoreceptors (Roddy et al, 2012), and retinal ganglion cells (Kim et al, 2013). Cellular protective functions of STC-1 have been attributed to its ability to reduce apoptosis (Huang et al, 2014; Kim et al, 2013; Tang et al, 2014), oxidative stress (Huang et al, 2012; Huang et al, 2015b; Kim et al, 2013; Liu et al, 2016; Nguyen et al, 2009; Roddy et al, 2012; Shi et al, 2014; Tang et al, 2014; Wu et al, 2014), and inflammation (Kanellis et al, 2004; Mohammadipoor et al, 2016; Tang et al, 2014; Wang et al, 2009), which are all pathways involved in RD (Ding et al, 2009).…”
mentioning
confidence: 99%
“…Cellular protective functions of STC-1 have been attributed to its ability to reduce apoptosis (Huang et al, 2014; Kim et al, 2013; Tang et al, 2014), oxidative stress (Huang et al, 2012; Huang et al, 2015b; Kim et al, 2013; Liu et al, 2016; Nguyen et al, 2009; Roddy et al, 2012; Shi et al, 2014; Tang et al, 2014; Wu et al, 2014), and inflammation (Kanellis et al, 2004; Mohammadipoor et al, 2016; Tang et al, 2014; Wang et al, 2009), which are all pathways involved in RD (Ding et al, 2009). We recently demonstrated that intravitreal injection(s) of recombinant human STC-1 delayed photoreceptor degeneration in the rapidly degenerating S334ter-3 rhodopsin transgenic rat and in the Royal College of Surgeons rat (Roddy et al, 2012).…”
mentioning
confidence: 99%